Social Determinants of Stroke as Related to Stress at Work among Working Women: A Literature Review - Susanna Toivanen (Stroke Research and Treatment)
In adult life, many of the social determinants of health are connected to working life. Yet, our knowledge of the role of work-related factors for the risk of stroke is fairly limited. In contemporary occupational health research, the Demand-Control Model (DCM) is frequently used to measure work stress. Previous literature reviews of the association of work stress and cardiovascular disease (CVD) do not include stroke as a specific outcome. Results regarding work stress and the risk of CVD are less evident in working women. With the focus on working women, the purpose of the present paper was to review the current research into the DCM in relation to stroke and to scrutinize potential gender differences. A literature search was performed and eight studies from three countries were identified. Based on the reviewed studies, there is some evidence that high psychological demands, low job control, and job strain are associated with increased stroke risk in women as well as in men. Any major reduction in deaths and disability from stroke is likely to come from decreasing social inequalities in health, and reducing work stress has a potential to contribute to a reduced risk of stroke in working populations.